Treatment of Unruptured Cerebral Aneurysms with the Mineralocorticoid Receptor Blocker Eplerenone—Pilot Study - Nagahiro, Shinji; Tada, Yoshiteru; Satomi, Junichiro; Kinouchi, Tomoya; Kuwayama, Kazuyuki; Yagi, Kenji; Nakajima, Kohei; Matsushita, Nobuhisa; Miyamoto, Takeshi; Yamaguchi, Tadashi; Shimada, Kenji; Korai, Masaaki; et al. (Journal of stroke and cerebrovascular diseases, 2018)
Currently there are no pharmacological therapies for patients with unruptured cerebral aneurysms. Elsewhere we showed that the mineralocorticoid receptor antagonist eplerenone prevented the formation of cerebral aneurysms in our ovariectomized hypertensive aneurysm rat model. The current pilot study evaluated whether it can be used to prevent the growth and rupture of cerebral aneurysms in hypertensive patients. Between August 2011 and May 2014, we enrolled 82 patients with 90 aneurysms in an open-label uncontrolled clinical trial. All provided prior informed consent for inclusion in this study, and all were treated with eplerenone (25-100 mg/d). The primary end points of our study were the rupture and enlargement of the cerebral aneurysms. Of the 82 patients, 80 (88 unruptured aneurysms) were followed for a mean of 21.3 months (153.4 aneurysm-years); 12 patients (15.0%) permanently discontinued taking the drug. One month after the start of eplerenone administration and throughout the follow-up period, eplerenone kept the blood pressure within the normal range. Most notably, no aneurysms smaller than 9 mm ruptured or enlarged. However, of 2 large thrombosed aneurysms, 1 enlarged and the other ruptured. The overall annual rupture rate was .65%; it was 13.16% for aneurysms larger than 10 mm; the overall annual rate for reaching the primary end points was 1.30%. Our observations suggest that eplerenone may help to prevent the growth and rupture of unruptured cerebral aneurysms smaller than 9 mm. To assess its potential long-term clinical benefits, large clinical trials are needed.